2015
DOI: 10.1021/acs.jpcc.5b03833
|View full text |Cite
|
Sign up to set email alerts
|

Multilamellar Nanoparticles Self-Assembled from Opposite Charged Blends: Insights from Mesoscopic Simulation

Abstract: Multilamellar nanoparticles (NPs) are spontaneously formed when mixing two components with opposite charges, meaningful for drug delivery. However, details of NPs association and mechanisms of this process remain largely unknown, due to the limitation of experimental technique. In this work, we use dissipative particle dynamics (DPD) simulation for the first time to determine the structure−property relationships of multilamellar NPs formed by charged blends. As a case study, a system with polyanionic fondparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…These results indicated that SQ-gem/EF NAs were stable with no signs of particle disruption, agglomeration or precipitation, probably due to the presence of a complementary amphiphilic compound such as EF in the NAs. Nie et al suggested that a regular multilamellar structure at the proper concentration ratio of components is a key factor for optimal stability [48]. The colloidal properties of the NAs were evaluated in this experiment at4 °C with regard to future administrations.…”
Section: Colloid Stability Of Sq-gem/ef Nasmentioning
confidence: 99%
“…These results indicated that SQ-gem/EF NAs were stable with no signs of particle disruption, agglomeration or precipitation, probably due to the presence of a complementary amphiphilic compound such as EF in the NAs. Nie et al suggested that a regular multilamellar structure at the proper concentration ratio of components is a key factor for optimal stability [48]. The colloidal properties of the NAs were evaluated in this experiment at4 °C with regard to future administrations.…”
Section: Colloid Stability Of Sq-gem/ef Nasmentioning
confidence: 99%
“…Analogously to the previous paper, the increased solubility of histidine units upon the protonation was treated by a significant decrease in the repulsion parameter between the protonated histidine and water. We are of the opinion that simulations of polyelectrolytes that do not take into account real physics and ignore electrostatic interactions [176][177][178][179][180][181][182][183][184][185][186], even though they are fast and can emulate some properties (if the interaction parameters are suitably set to reproduce experimental data), fail to describe correctly the general trends of the behaviour (not speaking of their prediction), simply because they do not capture the behaviour of counterions, the entropy of which acts as a decisive driving force of the electrostatic co-assembly.…”
Section: Studies Aimed At the Improvement Of Dpd Methodology And At Important Trends Of The Behaviourmentioning
confidence: 99%
“…The repulsive parameter αij between bead i and j lies on the underlying atomistic interactions which is linearly related to the Flory‐Huggins parameters as given by the following formulas: αij=αii+3.27χij where αii is equal to 78 . For binary components i and j, the Flory–Huggins parameter χij can be estimated by Eq.…”
Section: Simulation Methodsmentioning
confidence: 99%